2018
DOI: 10.3892/ol.2018.7814
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑499a‑5p inhibits osteosarcoma cell proliferation and differentiation by targeting protein phosphatase 1D through protein kinase B/glycogen synthase kinase 3β signaling

Abstract: A number of studies have attempted to elucidate the association between mircoRNAs (miRNAs/miRs) and cancer-associated processes. The aim of the present study was to determine how miR-499a-5p intervenes in human osteosarcoma cell proliferation and differentiation. The cancerous tissues and adjacent non-cancerous tissues of 62 patients with osteosarcoma (OS) were collected. miRNA microarray analysis revealed that 29 miRNAs were upregulated while 26 were downregulated, among which miR-499a-5p expression was the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…These results were consistent with previous finding on the antiproliferative activity of miR-499a-5p. 25 Similarly, the inhibitory roles of various miRNAs in tumorigenesis of NSCLC have been reported in previous studies. Meng et al showed that miR-377 plays an important role in the tumorigenesis of NSCLC by targeting astrocyte elevated gene-1, and may be a potential therapeutic target for lung cancer.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…These results were consistent with previous finding on the antiproliferative activity of miR-499a-5p. 25 Similarly, the inhibitory roles of various miRNAs in tumorigenesis of NSCLC have been reported in previous studies. Meng et al showed that miR-377 plays an important role in the tumorigenesis of NSCLC by targeting astrocyte elevated gene-1, and may be a potential therapeutic target for lung cancer.…”
Section: Discussionsupporting
confidence: 59%
“… 23 Among them, miR-499a-5p, has been shown to play a key role in cardiomyogenic differentiation of bone marrow-derived mesenchymal stem cells and has inhibitory effects on the proliferation and differentiation of osteosarcoma. 24 , 25 However, there is currently no data regarding the functions of miR-499a-5p in NSCLC. In this study, we evaluated the role of miR-499a-5p in the tumorigenesis of NSCLC, as well as the underlying molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated studies uncovered that miR-499a was decreased in several cancers, including pancreatic cancer [32], hepatocellular carcinoma [33] and oral squamous cell carcinoma [34], functioning as the tumor suppressor. In OS, it was found inhibiting OS cell proliferation [35], however, the biological function and underlying mechanisms of miR-499a in OSCs was unclear. In this study, by characterizing the down-stream mechanisms of TGFβ-induced EMT in OS, we found that miR-499a was significantly reduced upon TGFβ treatment.…”
Section: Discussionmentioning
confidence: 99%
“…16 MiR-499a-5p has gained increasing attention in cancer research because of its anti-tumor action. The aberrant downregulation of miR-499a-5p expression has been identified in oral squamous cell carcinoma, 17 osteosarcoma, 12 and lung adenocarcinoma; 13 however, little is known regarding its expression in CC. Here, in this study, we firstly determined the expression level of miR-499a-5p in CC tissues and cell lines by qRT-PCR and found that miR-499a-5p was significantly downregulated in CC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Liu et al found that the overexpression of miR-499a-5p repressed proliferation and differentiation of osteosarcoma cells by negatively regulating its target gene protein phosphatase 1D (PPM1D) through modulation of Akt/synthase kinase 3β (GSK-3β) signaling. 12 Additionally, it has been reported that miR-499a-5p promoted lung cancer cell proliferation, migration, and epithelial-mesenchymal transition (EMT) in vitro and enhanced tumor growth in vivo. 13 However, the expression of miR-499a-5p in CC tissues remains unclear, and whether it modulated the radiosensitivity of CC cells is still unknown.…”
Section: Introductionmentioning
confidence: 99%